PERAN PENDIDIK DALAM MEMBANGUN PERADABAN BANGSA MELALUI PENDIDIKAN KARAKTER - Chotimah, Chusnul (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
The development of civilization depends on the potential of human resourcesis managing. Human resource potential will be maximized when supported by advanced education. In other say, between education and civilization are the two things are directly proportional. Therefore, civilized nations provide dedicated space for education. The more space for the higher education of civilization that will be engraved. Opposite, a civilization that is weak because education does not have a dequate space. The essential values that includes the eighteen character value that discourse is not just a slogan but also requires real implementation and embedded in the character of students, which it could only be integrated through a learning process, a role model and habitus in education through the role of teacher. In genealogy, this article will examine the role of teacher in instilling the value of the character as the support base of civilization, carried out through five major roles namely: transferring, transforming, modeling, transcending, and inspiring. In the process of education, the role fifth isintegrative-mutually inclusive.Keywords: Role of Teacher, Civilization, Character Building